2023
DOI: 10.3389/fncel.2023.1110967
|View full text |Cite
|
Sign up to set email alerts
|

Does the functional polymorphism-1562C/T of MMP-9 gene influence brain disorders?

Abstract: Metalloproteinase-9 (MMP-9) is one of the most strongly expressed matrix metalloproteinases (MMPs) in the brain. The MMP-9 activity in the brain is strictly regulated, and any disruptions in this regulation contribute to a development of many disorders of the nervous system including multiple sclerosis, brain strokes, neurodegenerative disorders, brain tumors, schizophrenia, or Guillain-Barré syndrome. This article discusses a relationship between development of the nervous system diseases and the functional s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 112 publications
(166 reference statements)
0
1
0
Order By: Relevance
“…This Zn 2+ -activated protease is functionally related to various cell surface proteins, including integrins, TrkA and TrkB receptors, and plays essential roles in neurodevelopment and synaptic plasticity (Verslegers et al 2013 ; Vafadari et al 2016 ) and regulation of axonal myelination and pruning (Reinhard et al 2015 ). MMP9 polymorphisms are among the principal risk factors for sporadic ALS (Zawislak et al 2009 ; Pabian-Jewula and Rylski 2023 ), with results of postmortem studies of ALS patients showing MMP9 levels ~ 2.5-fold lower in the oculomotor nucleus as compared to lumbar MNs (Brockington et al 2013 ). Accordingly, Kaplan and co-workers reported higher expression of MMP9 in ALS-vulnerable MNs of the SOD1 mouse model, with its overexpression in wild-type MNs sufficient to trigger axonal dieback (Kaplan et al 2014 ).…”
Section: Intrinsic Factors Influencing Mn Vulnerability To Neurodegen...mentioning
confidence: 99%
“…This Zn 2+ -activated protease is functionally related to various cell surface proteins, including integrins, TrkA and TrkB receptors, and plays essential roles in neurodevelopment and synaptic plasticity (Verslegers et al 2013 ; Vafadari et al 2016 ) and regulation of axonal myelination and pruning (Reinhard et al 2015 ). MMP9 polymorphisms are among the principal risk factors for sporadic ALS (Zawislak et al 2009 ; Pabian-Jewula and Rylski 2023 ), with results of postmortem studies of ALS patients showing MMP9 levels ~ 2.5-fold lower in the oculomotor nucleus as compared to lumbar MNs (Brockington et al 2013 ). Accordingly, Kaplan and co-workers reported higher expression of MMP9 in ALS-vulnerable MNs of the SOD1 mouse model, with its overexpression in wild-type MNs sufficient to trigger axonal dieback (Kaplan et al 2014 ).…”
Section: Intrinsic Factors Influencing Mn Vulnerability To Neurodegen...mentioning
confidence: 99%
“…The data indicated that the MMP-9 polymorphism, even if it is not the leading player responsible for the development of many diseases, certainly does matter [14]. Until now, no one has demonstrated that MMP-9 expression is regulated by the MMP-9-1562C/T polymorphism in brain cells.…”
Section: Introductionmentioning
confidence: 99%